Bubble-Induced Rupture of Droplets on Hydrophobic and Lubricant-Impregnated Surfaces - Mullagura, Haritha N (Langmuir : the ACS journal of surfaces and colloids, 2020)
Bursting of bubbles is ubiquitous with numerous applications ranging from spraying of pesticides, drug delivery, and inkjet printing to forming emulsions. Understanding the parameters that influence the dynamics of bubble rupture is crucial to design systems with improved performance. Here, we experimentally investigate the behavior of air-bubble-induced rupture of a sessile droplet placed on hydrophobic and lubricant-impregnated surfaces (LIS). We demonstrate that the bubble dynamics inside a sessile droplet and subsequent rupture of the thinning film is dependent on the nature of the underlying substrate and the thermodynamic state of the droplet on the substrate. The growth of the bubble is shown to be dependent on the contact angle hysteresis of water and air on the substrate and the presence of a cloaking oil film around the water droplet. On a plain and textured surface with a high contact angle hysteresis, bubble-induced rupture initiates at the apex of the droplet. In the case of LIS that offers negligible pinning forces, the bubble-induced rupture of liquid shell initiates near the triple contact line. The dynamics of rupture of droplets placed on LIS is shown to be dependent on the viscosity of the impregnating and cloaking lubricant